Aboriginal youth summer camp in science and health science: a Western Canadian university review of 10 years of successes and learning. Issue 3 (2nd July 2020) - Cheeptham, Naowarat; Mahara, Star; Antoine, Misty; Insuk, Chadabhorn; Loy, Kara
ABSTRACT: Over the past ten years, a western-Canadian university has offered an annual on-campus summer science and health science camp for Aboriginal youth. The goal of this camp has been to enhance pathways to science and health science careers for high school students aged 13–15 years-old. The camp's core curriculum exposes youth to science and health sciences through fun and engaging activities. Students consistently reported that the camp helped strengthen connections between their learning in secondary school, potential university level education, and future career options in science and health science. This camp has been well received across British Columbia Aboriginal communities as evidenced by increasing enrollments and community member participation. As faculty and staff involved in the 10-year history of the summer camp, we reflect on our work for the purpose of informing others concerned with promoting science and health science careers for Aboriginal youth. Given a gap in the literature around planning and delivering successful science and health science-focused summer camps for Aboriginal youth, we offer this account of our successes and lessons learned for those planning or already engaged in implementing similar educational efforts.